Possible role of arbuscular mycorrhizal (AM) fungi on drought tolerance in Vigna unguiculata subsp. unguiculata (L.) Walp and Leucaena latisiliqua L. - Gowsalya Devi, A. P. (2018)
Pot culture experiments were carried out in sterilized soil to determine the effects of three AM fungi, Acaulospora scrobiculata, Glomus aggregatum and G. etunicatum, both individually as well as in combinations, on the plant growth and drought resistance of Vigna unguiculata and Leucaena latisiliqua. All plants were inoculated with Rhizobium sp. During the first 45 days all pots were watered to field capacity and the plants were then subjected to drought cycles by withholding water for 7 days. The plants were further subjected to 7 drought cycles. Inoculation of single endophyte G. etunicatum in V. unguiculata and A. scrobiculata in L.latisiliqua produced higher growth, biomass, nodule number, and percentage of root colonization. Proline content was higher in all the plants inoculated with G. etunicatum, whereas inoculation of G. aggregatum in Vigna unguiculata and G.etunicatum in L. latisiliqua resulted in higher tissue N, P and K contents. In double endophyte inoculations, A. scrobiculata and G. aggregatum in V. unguiculata; A. scrobiculata and(i.etunicatum in L. latisiliqua combinations were found to be highly effective.